Perbandingan Pemberian Aromaterapi Lavender Dan Lemon Terhadap Nyeri Persalinan Kala I Pada Ibu Bersalin Di Wilayah Puskesmas Cimanggu Pandeglang Banten Tahun 2022: Comparison of Giving Lavender and Lemon Aromatherapy to Pain in the First Stage of Labor for Mothers in the Cimanggu Pandeglang Health Center, Banten, 2022 - Yulyana, M (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: Pain during labor is unique and different for each individual, this is because the pain is influenced by fear or anxiety about childbirth. Excessive and prolonged labor pain will cause anxiety and psychological pressure, and it can affect the physical condition of the birthing mother, such as increased blood pressure, respiratory rate, and heart rate. There are many methods for dealing with labor pain. Methods: The research method was quasi-experimental with two group pre-test and post-test design. The number of samples was 30 respondents, and the sampling technique used purposive sampling and data analysis using Independent T-test. Results: The level of labor pain in the first stage of labor before and after giving lavender aromatherapy obtained an average value of 6,00; and after being given lavender aromatherapy, an average of 3,20 with an average difference of 2,80. The level of labor pain in the first stage of labor before and after giving lemon aromatherapy obtained an average value of 6,47; and after being given lemon aromatherapy, an average of 1,73 with an average difference of 4,74. There is a difference between giving lavender aromatherapy and lemon aromatherapy to the level of labor pain in the first stage of labor, with a significance level of 0,002. Discussion: The research concludes that there is a difference between giving lavender aromatherapy and lemon aromatherapy to the level of labor pain in the first stage of labor in women. Giving lemon and lavender aromatherapy can be applied thoroughly in Indonesian health services.